All-trans retinoic acid influences viability, migration and adhesion of U251 glioblastoma cells - Marjanović Vićentić, Jelena; Schwirtlich, Marija; Kovačević-Grujičić, Nataša; Stevanović, Milena; Drakulić, Danijela (Archives of Biological Sciences, 2017)
Glioblastoma (GBM) is one of the most aggressive and deadly forms of cancer. Literature data reveals that all-trans retinoic acid (ATRA) has anticancer effects on different types of tumor cells. However, data about the effects of ATRA on glioblastoma cells are contradictory. In this study, we examined whether ATRA treatment affects features of human glioblastoma U251 cells. To that end, the cells were treated with different concentrations of ATRA. Results obtained by MTT and the crystal violet assays imply that ATRA affected the viability of U251 glioblastoma cells in a dose- and time-dependent manner. Fluorescence staining of microtubule cytoskeleton protein α-tubulin revealed that ATRA induced changes in cell morphology. Using semi-quantitative RT-PCR we found that the expression of SOX3 and GFAP genes, as markers of neural differentiation, was not changed upon ATRA treatment. Thus, the observed changes in cell morphology after ATRA treatment are not associated with neural differentiation of U251 glioblastoma cells. The scratch-wound healing assay revealed that ATRA changed the mode of U251 cell migration from collective to single cell motility. The cell-matrix adhesion assay demonstrated that the pharmacologically relevant concentration of ATRA lowered the cell-matrix adhesion capability of U251 cells. In conclusion, our results imply that further studies are needed before ATRA could be considered for the treatment of glioblastoma. https://doi.org/10.2298/ABS170327016M Received: March 27, 2017; Revised: May 23, 2017; Accepted: June 2, 2017; Published online: June 12, 2017 How to cite this article: Marjanović Vićentić J, Schwirtlich M, Kovačević-Grujičić N, Stevanović M, Drakulić D. All-trans retinoic acid influences viability, migration and adhesion of U251 glioblastoma cells. Arch Biol Sci. 2017;69(4):699-706.